Using Interpretative Phenomenological Analysis (IPA) to provide insight into female sexual difficulties - O'Mullan, C.; Doherty, M.; Coates, R.; Tilley, Peter (Brunner - Routledge, 2017)
© 2017 College of Sexual and Relationship Therapists Sexual experiences and behaviour are particularly open to social and cultural influences; this is especially true within the area of female sexuality. While research into the social and cultural aspects of sexuality proliferated throughout the 1970s and 1980s, contemporary biomedical approaches to sexuality research have largely ignored the complex interplay of such dimensions. In this methodological paper, we reflect upon how Interpretative Phenomenological Analysis (IPA) can be used by sexuality researchers to explore women's sexual experiences and difficulties and to locate these experiences within cultural and social contexts. By drawing on the authors’ experiences of using IPA to explore how women cope with the sexual side effects of antidepressant medication, we provide an overview of IPA as a research approach, briefly summarise studies which have used IPA to explore women's sexual experiences and difficulties and outline a series of steps on how to conduct an IPA study. It is hoped that this paper will stimulate debate, and encourage sexuality researchers to explore and consider the use of IPA to contribute to a research agenda based on women's individual needs and desires.